Self-Efficacy and Quality of Life Among Farmers in Indonesia: A Literature Review - Hardianto, Widodo; Rasni, Hanny; Susumaningrum, Latifa Aini; Kurdi, Fahruddin; Fitria, Yeni (Al-Hijrah Indonesia, 2024)
Background: The level of self-efficacy plays a role in influencing the quality of life of hypertension patients. Self-efficacy helps individuals cope with and maintain hypertension health conditions that can affect their quality of life. 55.18% of the total population in Indonesia work in the agricultural sector. Purpose: The aim of this literature review study is to explore the correlation and publications providing information on self-efficacy related to the quality of life of elderly farmers. Methods: This literature review study uses a narrative review approach and analyzes six articles from sources such as Google Scholar, ScienceDirect, and PubMed. Results: The findings suggest a significant association between self-efficacy levels and the quality of life of elderly hypertension patients in Indonesia. Hypertensive elderly farmers with high self-efficacy tend to have a better quality of life. A significant relationship was also found between self-efficacy, subjective well-being in tobacco farmers, and adherence to a healthy lifestyle among hypertension patients. Conclusion: The study concludes that factors such as gender, age, education, and life experience influence self-efficacy. Quality of life is influenced by age, education, gender, marital status, duration of hypertension, and occupation. High levels of self-efficacy are positively correlated with the ability of the elderly to face hypertension challenges and improve their quality of life. Nurses should provide education and motivation to hypertension patients to enhance their self-efficacy.